2019
DOI: 10.1167/iovs.19-27322
|View full text |Cite
|
Sign up to set email alerts
|

VISTA Is Crucial for Corneal Allograft Survival and Maintenance of Immune Privilege

Abstract: Citation: Kunishige T, Taniguchi H, Ohno T, Azuma M, Hori J. VISTA is crucial for corneal allograft survival and maintenance of immune privilege. Invest Ophthalmol Vis Sci. 2019;60:4958-4965. https://doi.org/ 10.1167/iovs.19-27322 PURPOSE. V-domain immunoglobulin suppressor of T cell activation (VISTA) is a novel immune checkpoint receptor and ligand for regulating T cell proliferation and cytokine production. The purpose of the present study was to determine the role of VISTA in the immune privilege of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…We have expanded upon these data and showed that selective targeting of donor alloreactive T cells is sufficient for the anti‐VISTA prophylactic effect in GVHD . Of relevance, a recent study found that VISTA was expressed by myeloid cells of the corneal stroma and that genetic deficiency or blockade of VISTA significantly reduced corneal allograft survival . We have observed similar results where VISTA‐deficiency or blockade also markedly reduced skin graft tolerance and survival and superseded the immunosuppressive effects of CD40L blockade (ElTanbouly and LeMercier, unpublished observations).…”
Section: Vista‐deficiency Enhances Immunitymentioning
confidence: 68%
“…We have expanded upon these data and showed that selective targeting of donor alloreactive T cells is sufficient for the anti‐VISTA prophylactic effect in GVHD . Of relevance, a recent study found that VISTA was expressed by myeloid cells of the corneal stroma and that genetic deficiency or blockade of VISTA significantly reduced corneal allograft survival . We have observed similar results where VISTA‐deficiency or blockade also markedly reduced skin graft tolerance and survival and superseded the immunosuppressive effects of CD40L blockade (ElTanbouly and LeMercier, unpublished observations).…”
Section: Vista‐deficiency Enhances Immunitymentioning
confidence: 68%
“…In a model of experimental asthma, VISTA deficiency and blockade exacerbated Th2 responses and type II immunity ( 11 , 22 ), whereas an anti-VISTA agonistic antibody reduces disease severity and suppressed lung inflammation ( 22 ). There are reported roles of VISTA deficiency in several other inflammatory diseases including psoriasis, transplant rejection, acute hepatitis, and indicate a potential value of VISTA agonists in these immunopathologies ( 12 , 23 , 24 ).…”
Section: Targeting Vista With Agonists Suppresses Multiple Inflammatomentioning
confidence: 99%
“…In the eye, VISTA mRNA is constitutively expressed in the cornea, and the expression of VISTA is localized to CD11b + cells on the corneal stroma [30]. The survival of corneal allograft in the recipients treated with anti-VISTA mAb was less than that of the control.…”
Section: Vista(pd-1h)mentioning
confidence: 99%
“…As shown in Table 1, various immunomodulatory factors are expressed in corneal endothelial cells and in the iris-ciliary body. We have revealed that inhibitory costimulatory signaling molecules such as programmed death ligand-1 (PD-L1, B7-H1) [28], inducible costimulatory molecule ligand (ICOSL, B7-H2, B7-related protein (B7RP)-1) [29], V-domain Ig suppressor of T cell activation (VISTA, PD-1H) [30], glucocorticoid-induced tumor necrosis factor (TNF) receptor family-related protein ligand (GITRL) [31], and galectin-9 [32], are constitutively expressed in the corneal tissue and involved in immune suppression in the cornea (Figure 1). These inhibitory costimulatory signal molecules play an important role in the regulation of antigen-specific T-cell-mediated immune responses.…”
Section: Immune Suppressive Microenvironment In the Anterior Segment mentioning
confidence: 99%
See 1 more Smart Citation